2019
DOI: 10.17765/2176-9168.2019v12n2p363-375
|View full text |Cite
|
Sign up to set email alerts
|

Análise Econômica Da Farinha De Silagem Ácida De Resíduos De Pirarucu Em Rações De Poedeiras Comerciais Leves

Abstract: Este estudo objetivou analisar a viabilidade econômica da inclusão de farinha de silagem ácida de resíduos de pirarucu em rações de poedeiras comerciais leves. O período experimental foi de 84 dias divididos em quatro períodos de 21 dias cada. Foram utilizadas 168 poedeiras da linhagem Hissex White com 73 semanas de idade. O delineamento experimental foi o inteiramente casualizado constituído de sete tratamentos correspondentes a níveis de inclusão de farinha de silagem ácida de resíduos de pirarucu (0; 0,5; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…That's why there is no need to sell heavier fish, as pirarucu loin in weight classes 3, 4 and 5 already meets the nutritional demand of the market. Therefore, this is an alternative to reduce production costs, a factor that has discouraged fish farmers from raised pirarucu (Batalha et al, 2019;Gotardi, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…That's why there is no need to sell heavier fish, as pirarucu loin in weight classes 3, 4 and 5 already meets the nutritional demand of the market. Therefore, this is an alternative to reduce production costs, a factor that has discouraged fish farmers from raised pirarucu (Batalha et al, 2019;Gotardi, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Research around the world has shown that diets rich in lipids tend to affect the concentrations of minerals in the body of fish, causing a lower absorption of minerals such as calcium, resulting in greater renal and/or fecal excretion (CORWIN, 2003). Induction of urinary calcium excretion when there are high concentrations of free fatty acids in plasma (BATALHA et al, 2017), considering such premises, a negative interaction between lipids and mineral deposition in muscle tissue is considered (DUARTE et al, 2021). It is important to highlight that the ingested amount of an element and the mineral versus mineral interactions that occur when they compete for the same absorption site because they have physicochemical similarities, and the excess of one will harm the use of the other (DUARTE et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tambaqui is of the main sources of animal protein for the Amazon population and an important source of fatty acids, such as PUFAs like the ones mentioned EPA and DHA, proteins and minerals (LIMA et al, 2018). It has characteristics such as easy digestibility, due to high biological value proteins (BATALHA et al, 2017). As they efficiently provide energy and essential fatty acids, lipids are important components of the diet.…”
Section: Introductionmentioning
confidence: 99%
“…To add more technical and scientific information, the inclusion of fish processing residues in animal feed has shown promising results. Researches demonstrate the potential of its use in the formulation of feeds, for example, the research by Batalha et al (2019), andBrelaz et al (2021), studying the use of fish residues oil in the feeding of laying hens, concluded that it can be used as an additive in rations at a level of 1.5%, and can be used as an alternative feed, reducing production costs. Stoneham et al (2018), found that tilapia fed with rations enriched with n-3 from fish oil showed a high concentration of n-3 in their meat and rapid growth, demonstrating that it is possible and viable to use and produce by-products with added value of the visceral fat residues.…”
Section: Indexes Formulas Valuesmentioning
confidence: 99%
“…These results are important due to the search for foods of good nutritional quality that can minimize the costs of feeding in fish farming, as well as the use of residues rich in proteins and lipids that until then would have been residuesd, its proper use can minimize production costs, since food has become the most expensive item in fish farming (BATALHA et al, 2017). Its use in fish feeding tends to provide nutritional and economic advantages, especially in Brazilian regions that suffer from logistical limitations for grains and high-value raw materials (CRUZ et al, 2016).…”
Section: Referencesmentioning
confidence: 99%